Agricultural extension in Africa. Proceedings of an international workshop, Yaounde, Cameroon, Volume II. - Wolf, Judith N. (Technical Centre for Agricultural and Rural Cooperation, 1996)
Drawing on the experiences of research and development agencies, the handbook offers an alternative to the use of high-input technologies to achieve sustainable agriculture in Africa.